Interactions between Keggin Anions in Water: The Higher Their Charge, the Higher Their Condensation? A Simulation Study (Eur. J. Inorg. Chem. 10‐11/2013). Issue 10 (26th March 2013) - Chaumont, Alain; Wipff, Georges
Abstract : The front cover picture shows (top left) a snapshot of a simulated box of water containing [AlW12 O40 ] 5– POM anions and their H3 O + counterions, forming local aggregates (zoomed). Indeed, the free energy profile ΔG( d ) calculated as a function of the POM··· POM distance in water (top right) displays a minimum for the "contact" like‐anion pair, corresponding to a high density of bridging counterions (inset, left). POMs also adsorb at the aqueous interface with graphite (bottom). The background is an extended view of the solution. Details are discussed in the article by G. Wipff and A. Chaumont on p. 1835 ff.